Propagation of sound waves of finite amplitude in a horn at frequencies below the cut-off frequency - ZAMORSKI, T. (Archives of Acoustics, 2014)
An investigation of the wave of finite amplitude in hyperbolic horn with annular cross-section is described. The fluid in the horn is assumed to be nondissipative. The equation of the sound wave propagation in the horn is solved for the case of frequencies below the cut-off frequency. The analysis is qiven in Lagrangian coordinates.